Exploring Factors Influencing Reading Comprehension Beyond Habits in Students: Mengeksplorasi Faktor-Faktor yang Mempengaruhi Pemahaman Membaca di Luar Kebiasaan pada Siswa - Putra, Raeyen Anggara; Taufiq, Wahyu (Indonesian Journal of Education Methods Development, 2024)
This study investigates how students' reading habits impact their reading comprehension. Using a quantitative survey method with questionnaires and tests, data was collected and analyzed with SPSS. Results showed no significant correlation between students' reading habits and comprehension, suggesting other factors are at play. The study recommends schools implement dedicated literacy time to enhance critical thinking, vocabulary, and overall reading motivation, thereby improving comprehension. Highlight: Examines reading habits' impact on comprehension. Uses quantitative research and surveys. Emphasizes dedicated literacy time. Keywords: Reading habits, Reading comprehension, Quantitative research, Literacy time,Student motivation,